Spinel-structured surface layers for facile Li ion transport and improved chemical stability of lithium manganese oxide spinel - Lee, Hae Ri; Seo, Hyo Ree; Lee, Boeun; Cho, Byung Won; Lee, Kwan-Young; Oh, Si Hyoung (ELSEVIER SCIENCE BV, 2017)
Li-ion conducting spinel-structured oxide layer with a manganese oxidation state close to being tetravalent was prepared on aluminum-doped lithium manganese oxide spinel for improving the electrochemical performances at the elevated temperatures. This nanoscale surface layer provides a good ionic conduction path for lithium ion transport to the core and also serves as an excellent chemical barrier for protecting the high-capacity core material from manganese dissolution into the electrolyte. In this work, a simple wet process was employed to prepare thin LiAlMnO4 and LiMg0.5Mn1.5O4 layers on the surface of LiAl0.1Mn1.9O4. X-ray absorption studies revealed an oxidation state close to tetravalent manganese on the surface layer of coated materials. Materials with these surface coating layers exhibited excellent capacity retentions superior to the bare material, without undermining the lithium ion transport characteristics and the high rate performances. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: X-RAY-ABSORPTION; CATHODE MATERIAL; LIMN2O4 NANORODS; CAPACITY LOSSES; RATE CAPABILITY; PERFORMANCE; DISSOLUTION; POWER; MN; SPECTROSCOPY